SCIENCE ADVENTURES: PRESCHOOLERS EXPLORATION OF NATURE - Murniasih S, Ni Putu; Putra, Gusti Ngurah; Yudana, Wayan (JARITA : Journal of Children’s Education and Learning Research, 2025)
This study entitled "Science Adventure: Exploring Nature for Early Childhood" aims to analyze the impact of nature exploration-based learning methods on early childhood development. This study was conducted for 3 months from June to August. The subjects of the study involved 30-40 children aged 4-6 years from two early childhood education institutions (PAUD) in Palu, namely TK Negeri Pembina Palu and TK Kasih Bangsa Palu. The approach used was descriptive qualitative, which allowed researchers to explore the influence of nature exploration in improving children's observation skills, curiosity, environmental awareness, and social skills. Research data were collected through surveys and interviews with teachers and parents to obtain an in-depth picture of the learning process. The results showed that this learning method significantly increased children's involvement in the learning process, increased their curiosity about the environment, and improved their social skills by interacting with peers. The results indicate that nature exploration should be included in the PAUD curriculum because it greatly helps the overall development of early childhood.